Issues and Challenges of Inclusive Education for Socially, Economically and Educationally Backward Children in Teaching Learning - Bushan Kumar (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2018)
Inclusive education not particularly for students with handicaps but rather additionally critical for instructively, socially and financially in reverse youngsters or understudies in the general public on the grounds that the training is claim for the satisfaction of the necessities and requests of the individual and society. This paper analyzed issues and challenges faced children with educationally, socially and economically backwards children or students and disabled in the society with special reference to teaching learning process. It is well known that all educational policies promote inclusion as the major idea in a contemporary system of education. Children with disabilities are still faced with a lot of challenges in realizing their right to education and they are one of the most marginalized and excluded groups in education. In addition to that the paper illustrated that issues and challenges faced the Students with Disabilities and SCs and STs in teaching learning process and also suggest the strategies to overcome the barriers and issues for the improvement of the disabilities children in teaching learning process. “If a child can’t learn the way we teach, maybe we should teach the way that they learn”———- Ignaicio Estrada